2015
DOI: 10.12659/msm.892542
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Prevention and Treatment of Cognitive Impairment in the Elderly

Abstract: The aim of this study is to present the available and verified methods of prevention of cognitive decline in healthy older adults and to review clinical trials of therapies to improve impaired cognitive performance. We discuss data about the actual possibility of pharmacological treatment, usefulness of physical exercises, and effectiveness of different cognitive training methods.In a separate chapter we discuss why older people cope much better in life challenges then it would appear from the measurements mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Previous studies indicate that the annual conversion rate from MCI to dementia is 10–15% and that approximately 50% of patients with MCI will progress to Alzheimer's disease (AD) within 4 years 4. Current guidelines recommend applying interventions for MCI and dementia as early as possible in order to slow cognitive decline and preserve the quality of life 56…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that the annual conversion rate from MCI to dementia is 10–15% and that approximately 50% of patients with MCI will progress to Alzheimer's disease (AD) within 4 years 4. Current guidelines recommend applying interventions for MCI and dementia as early as possible in order to slow cognitive decline and preserve the quality of life 56…”
Section: Introductionmentioning
confidence: 99%
“…The 8-step application of the walker requires cognitive ability. Up to 25% of people aged 70 years or above, suffer mild cognitive impairment (MCI) [11]. This means, their cognitive capacity is below the person’s expected age average.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, other studies have indicated that hypertension, hyperuricemia, and hypercholesterolemia may be associated with cognitive functions [ 34 36 ], but this was not found in the present study, perhaps due to the differences in methodology, intervention, course of diseases, and comorbidities. Methods currently used to prevent cognitive decline in elderly people with chronic diseases are pharmacological interventions, physical exercises, and cognitive training using mental exercises [ 37 ]. After training, there are moderate benefits in language, self-rated anxiety, and functional ability, and moderate improvements in episodic memory, semantic memory, executive functioning, working memory, and visual-spatial ability, as well as in attention processing speed, MMSE, self-rated memory problems, quality of life, activities of daily life, and self-rated depression [ 38 ].…”
Section: Discussionmentioning
confidence: 99%